Comparative Assessment of Knee Motion Monitoring Technologies [Diz Hareketi Izleme Teknolojilerinin Kar sila stirmali Degerlendirmesi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
Realizing 3D human models digitally is a difficult, yet continually required task. Numerous technologies are utilized to create these models. Due to the variety of technologies used, an evaluation and benchmarking is necessary. This is a comparative study of four such technologies. We compare a wearable textile sensor based motion capture system we designed and implemented to an RGB camera based, depth sensor based, and an inertial measurement unit based motion capture system. The four motion capture systems have been evaluated based on measures such as reliability, ease of use, universality, cost, sensitivity to atmospheric conditions, and flexibility. The preliminary preparations and test conditions for the realization of this comparative study are explained in this paper. Finally, the results of experimentation on one joint have been presented. © 2019 IEEE.
Keywords: Dijital Modelling; Joint Motion; Mocap; Motion Capture; Textile Sensor; Wearable Sensor